Handling qualitative data : a practical guide - Richards, Lyn , 1944- (SAGE, 2009)
This bestselling book has been extensively revised for the new edition with the latest on qualitative data analysis software. It also comes with a brand new companion website featuring pieces of real research which the author provides commentary on